Energy Drink Induced Lipid Peroxidation and Oxidative Damage in Rat Liver and Brain When Used Alone or Combined with Alcohol. Issue 4 (17th March 2017) - Reis, Rengin; Charehsaz, Mohammad; Sipahi, Hande; Ekici, Asiye Işın Doğan; Macit, Çağlar; Akkaya, Hatice; Aydın, Ahmet
Abstract: Energy drinks (ED) are containing large doses of metabolic stimulants and its use with ethanol has increased dramatically among young adults. In this study, we examined the effects of ED exposure either alone or in combination with ethanol on oxidative stress parameters including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH‐Px), and lipid peroxidation parameter malondialdehyde (MDA) in rat. Some histopathological findings were also evaluated. ED exposure led to a dose‐dependent increase in liver MDA compared to the control indicating oxidative damage. Histopathological findings also revealed that ED alone may generate liver damage. Ethanol exposure increased MDA level and SOD, CAT, and GSH‐Px activity in both the brain and the liver. The combination of ethanol and ED produced greater damage which is considered by further increases in SOD and GSH‐Px activity in the brain. Similar results for MDA were observed in both the liver and brain as well. Our findings suggest that ED consumption alone or combination with ethanol may represent a significant public health concern.